2015
DOI: 10.1016/j.aller.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of coagulation in chronic urticaria in relation to disease severity and activity

Abstract: We conclude that activation of the coagulation cascade occurs in CSU, and we demonstrate the novel finding that activated factor VII levels are significantly reduced after medical therapy, confirming the implication of the extrinsic pathway activation in CSU. Future controlled studies may investigate the role of anticoagulant therapy in refractory chronic urticaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
16
0
4
Order By: Relevance
“…observed an increase in prothrombin fragment 1 + 2, D‐dimer and CRP in patients with CSU and proposed that these markers correlate with disease severity. The activation of coagulation/fibrinolysis in patients with CU parallels disease activity and decreases during remission . These findings should prompt further studies that aim to investigate the predictive value of these markers for CSU severity and prognosis.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…observed an increase in prothrombin fragment 1 + 2, D‐dimer and CRP in patients with CSU and proposed that these markers correlate with disease severity. The activation of coagulation/fibrinolysis in patients with CU parallels disease activity and decreases during remission . These findings should prompt further studies that aim to investigate the predictive value of these markers for CSU severity and prognosis.…”
Section: Resultsmentioning
confidence: 91%
“…The activation of coagulation/ 89 75 ASST positivity is a significant predictor of better response to treatment fibrinolysis in patients with CU parallels disease activity 72,74 and decreases during remission. 72,75 These findings should prompt further studies that aim to investigate the predictive value of these markers for CSU severity and prognosis.…”
Section: Laboratory Markers Of Severity and Prognosismentioning
confidence: 99%
“…Such phenomenon, which is clearly associated with disease severity (2), seems to occur via the activation of the extrinsic pathway of the coagulation cascade (1). This finding was confirmed over time by several research groups (3)(4)(5)(6), one of whom also showed that the activation of the extrinsic pathway of the coagulation might in turn activate the intrinsic pathway also, eventually producing a hyper-coagulable pattern (7). The activation of the coagulation / fibrinolysis system is possibly a consequence of the hyper-expression of tissue factor by activated eosinophils (8), although also endothelial cells seem able to play a role in this sense (9).…”
Section: Introductionmentioning
confidence: 79%
“…The pathogenesis of chronic urticaria involves both the intrinsic and extrinsic coagulation pathway [13,19,20], although the precise underlying pathogenetic mechanisms are largely unknown. It is well established that thrombin enhances vascular permeability, and activates and degranulates mast cells, thus generating anaphylatoxin C5a [21].…”
Section: Discussionmentioning
confidence: 99%